Update Manajemen Perioperatif pada Gangguan Tiroid dan Adrenal - Brilliant Van Fitof S.R. (PT Dexa Medica, 2025)
Surgical patients with endocrine disorders require special consideration during perioperative evaluation and postoperative management. Several endocrine disorders encountered in the perioperative period include thyroid and adrenal diseases. Both conditions require optimal perioperative preparation to ensure that intraoperative and postoperative interventions proceed without complications. This preparation involves the collaboration of various medical disciplines, ranging from primary care physicians to consultant physicians in the hospitals. Patients with thyroid disorders require thorough preoperative assessment to prevent complications such as thyroid storm, which may occur during or after surgery. A similar approach is essential for patients with adrenal insufficiency. This article discusses the perioperative management in endocrine disorders, particularly thyroid and adrenal diseases, to enable clinicians such as surgeons, anesthesiologists, and internists provide appropriate therapeutic approaches for patients.